Characterization and Review of Dual Composite Cathodes LSCF-SDC/YSZ-SDC for Intermediate to Low Temperature Solid Oxide Fuel Cell - Abd.Rahman, Hamimah; Shaifull Zaman, Sharmine Wani Zakirah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Solid oxide fuel cell (SOFC) performance is highly dictated by the ohmic loss of the electrolyte and the resistance due to the cathodic polarization. To reduce the large polarization losses, dual composite cathodes have been introduced. The objectives of this research are to fabricate the LSCF-SDCC/YSZ-SDCC and LSCF-SDC/YSZ-SDC dual composite cathodes powders via ball milling process and evaluate the influence of dual cathode composition and carbonate on the characteristics on physical, morphology and chemical bonding of cathode. In this study, the cathode composite powder is developed from mixture of YSZ-SDC electrolyte powders will be mixed with various ratio 50:50, 60:40 and 70:30 wt%. Powder mixing was done through ball milling method. After mixing, YSZ-SDC electrolyte powders were calcined at 950℃. The morphology of YSZ-SDC powder showed intergranular pores textures are observed at the contact of YSZ and SDC due to SDC lower melting point compared to YSZ which made SDC easily diffuse into YSZ. No additional phase formation is presented in XRD patterns which indicates that there are no crystalline impurities. There is no other chemical bond pattern on side A and B such as carbon. Therefore, YSZ-SDC combination will work together to improve the SOFC conductivity and it is expected to allow the cell operates at intermediate to low temperature.